Correlations between schizophrenia and lichen planus: a two-sample bidirectional Mendelian randomization study - Chen, Guan-Yu; Fu, Ling-ling; Ye, Bin; Ao, Man; Yan, Ming; Feng, Hong-Chao (Frontiers in Psychiatry, 2023)
Background: Several existing studies have shown a correlation between schizophrenia and lichen planus (LP). However, the causality of this relationship remains uncertain. Thus, this study aimed to examine the causal association between schizophrenia and LP.Methods: A two-sample Mendelian randomization (MR) study was carried out to investigate whether schizophrenia is causally related to LP and vice versa,. and genetic variants in this study were taken from previous genome-wide association studies. We used the inverse variance weighted (IVW) method as the main analysis. Furthermore, several sensitivity analyses were performed to assess heterogeneity, horizontal pleiotropy, and stability.Results: Our results show that schizophrenia has a protective effect on LP (OR=0.881, 95%CI= 0.795-0.975, P=0.015). Conversely, we observed no significant relationship between LP and schizophrenia in reverse MR analysis (OR=0.934, 95%CI= 0.851-1.026, P=0.156).Our two-sample Mendelian randomization study supports a significant causal relationship between LP and schizophrenia and finds that schizophrenia can reduce the incidence of LP. This is in contrast to previous findings and provides new insights into the relationship between LP and schizophrenia, but the exact mechanism needs further investigation.